Analisis Peran Kejaksaan Terhadap Pelaksanaan Putusan Pengadilan Pada Kasus Penyerobotan Tanah - Sri Imelda Ayu Dude; Robby Waluyo Amu; Leni Dwi Nurmala (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Land grabbing is a form of unlawful act, namely an act of abuse of authority over land ownership rights. Acts of encroachment can take the form of occupying land, installing fences, or eviction of land owners and so on. The act of illegally grabbing land is an unlawful act, which can be classified as a criminal act as stated in the provisions of the Criminal Code. The problem approach used in this writing is the normative juridical method. Primary data collection techniques are obtained by conducting searches, inventories and reviewing regulations using literature studies including statutory regulations, books and articles in journals and scientific works. Deductive analysis techniques are used to analyze data with a starting point or based on general rules, then a specific conclusion is drawn. The mechanism for resolving land grabbing cases that occur in the community can be carried out through deliberation or mediation, litigation, non-litigation, through the role of law enforcement officials, resolution through arbitration institutions. As for the role of the prosecutor's office in implementing court decisions in cases of land grabbing, the main role of the prosecutor's office in this context is as the implementer of court decisions that have permanent legal force. The prosecutor's office is responsible for ensuring that the implementation of these decisions is carried out. The government's suggestion is to provide information to the public by means of outreach, appeals and information, especially about land ownership and the prosecutor's office as the implementer of court decisions can provide protection to people who have land rights.